Race development and performance-determining factors in a mass-start cross-country skiing competition - Seeberg, T. M.; Kocbach, J.; Wolf, H.; Talsnes, R. K.; Sandbakk, Ø. B. (Frontiers in Sports and Active Living, 2023)
Introduction: Although five of six Olympic events in cross-country skiing involve mass-starts, those events are sparsely examined scientifically. Therefore, in this study, we investigated speed profiles, pacing strategies, group dynamics and their performance-determining impact in a cross-country skiing mass-start competition.